New records of anisakid nematodes from marine fishes off New Caledonia, with descriptions of five new species of Raphidascaris (Ichthyascaris) (Nematoda, Anisakidae) - Moravec, František; Justine, Jean-Lou (Parasite (Paris, France), 2020)
Recent examinations of anisakid nematodes (Anisakidae) from marine fishes off New Caledonia, collected in the years 2003-2008, revealed the presence of the following five new species of Raphidascaris Railliet et Henry, 1915, all belonging to the subgenus Ichthyascaris Wu, 1949: Raphidascaris (Ichthyascaris) spinicauda n. sp. from the redbelly yellowtail fusilier Caesio cuning (Caesionidae, Perciformes); Raphidascaris (Ichthyascaris) fasciati n. sp. from the blacktip grouper Epinephelus fasciatus (Serranidae, Perciformes); Raphidascaris (Ichthyascaris) nudicauda n. sp. from the brushtooth lizardfish Saurida undosquamis (Synodontidae, Aulopiformes); Raphidascaris (Ichthyascaris) euani n. sp. from the Japanese large-eye bream Gymnocranius euanus (Lethrinidae, Perciformes); and Raphidascaris (Ichthyascaris) elopsis n. sp. from the Hawaiian ladyfish Elops hawaiensis (Elopidae, Elopiformes). An additional two congeneric species, R. (I.) etelidis Moravec et Justine, 2012 and R. (I.) sillagoides (Bruce, 1990) were found in the deep-water red snapper Etelis carbunculus (new host record) and the deepwater longtail red snapper Etelis coruscans (both Lutjanidae, Perciformes), and the silver sillago Sillago sihama (Sillaginidae, Perciformes) (new host and geographical records), respectively. Two unidentified congeneric species, Raphidascaris (Ichthyascaris) sp. 1 from the trumpet emperor Lethrinus miniatus (Lethrinidae, Perciformes) and Raphidascaris (Ichthyascaris) sp. 2 from the white-spotted puffer Arothron hispidus (Tetraodontidae, Tetraodontiformes) were recorded. Moreover, two species of Hysterothylacium Ward et Magath, 1917, H. alatum Moravec et Justine, 2015 and H. epinepheli (Yamaguti, 1941), were found in the leopard coralgrouper Plectropomus leopardus (type host) and the highfin grouper Epinephelus maculatus (new host) (both Serranidae, Perciformes), respectively. This is the second finding of H. epinepheli since its original description in Japan 79 years ago. Most species are described based on light and electron microscopical studies.
Keywords: potrava z moře (živočišná); South Pacific; New Caledonia; nemoci ryb; Fish Diseases; Japonsko; Nová Kaledonie; Anisakis; Female; Microscopy, Electron, Scanning; zvířata; Japan; ženské pohlaví; Male; Aulopiformes; Elopiformes; mikroskopie elektronová rastrovací; Seafood; Nematode parasite; Anisakiasis; Ascaridoidea; Animals; anisakióza; mužské pohlaví; Perciformes